2020
DOI: 10.1371/journal.pone.0234956
|View full text |Cite
|
Sign up to set email alerts
|

Involuntary ambulatory triage during the COVID-19 pandemic – A neurosurgical perspective

Abstract: Background The coronavirus disease 2019 (COVID-19) pandemic poses an unprecedented challenge to health-care systems around the world. As approximately one-third of the world´s population is living under "lockdown" conditions, medical resources are being reallocated and hospital admissions are limited to emergencies. We examined the decision-making impact of these actions and their effects on access to hospital treatment in patients with neurosurgical conditions. Methods This retrospective cohort study analyzes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 9 publications
2
15
0
1
Order By: Relevance
“…Contrary to what was observed in Germany, where emergency admissions decreased by 44.7% ± 0.7% during the pandemic, we observed an increase of 30% in medical evaluations in our emergency department. 65 The number of neurosurgical beds was significantly decreased (approximately a 70% reduction at our center), which is similar to a report from Europe. 66 This may be due to large neurosurgery centers in Mexico being reconverted as COVID-19 centers, and therefore their patient populations were referred to our hospital.…”
Section: Discussionsupporting
confidence: 89%
“…Contrary to what was observed in Germany, where emergency admissions decreased by 44.7% ± 0.7% during the pandemic, we observed an increase of 30% in medical evaluations in our emergency department. 65 The number of neurosurgical beds was significantly decreased (approximately a 70% reduction at our center), which is similar to a report from Europe. 66 This may be due to large neurosurgery centers in Mexico being reconverted as COVID-19 centers, and therefore their patient populations were referred to our hospital.…”
Section: Discussionsupporting
confidence: 89%
“…A similar trend in 2 non-LMIC hospitals is observed, where neurological emergency admissions during the lockdown in Germany declined by 44.7%. The consequences of this morbidity and mortality remain to be seen 22 (#206, Level II). Emergency department (ED) visits declined by 23% for myocardial infarction, 20% for stroke, and 10% for hyperglycemic crisis between March and May 2020 compared to 10 weeks prior to the emergency declaration for COVID-19 in the United States 23 (#150, Level VII).…”
Section: Interruption Of Essential Servicesmentioning
confidence: 99%
“…Our tertiary medical center has a catchment area population of 2.2 million, who live in a rather rural area of 20,000 km 2 . Consequently, the distance patients have to cover to get to a health care provider, especially in the case of a nationwide lockdown, appears to be an interesting aspect.…”
Section: Distance To the University Medical Center Regensburgmentioning
confidence: 99%
“…In comparable centers in Germany, neurosurgical emergency admissions also strongly declined during lockdown. 2,3 Another center in Helsinki, however, did not find any changes in the number of ICU admissions due to traumatic brain injury (TBI) or subarachnoid hemorrhage. 4 In the larger European perspective, Mathiesen et al found in a survey study that 18 of 25 centers reported a lower number of ICU-treated TBI patients, whereas their investigation focused on the resource-saving measurements that were taken rather than the factors concerning the patients being admitted to the emergency unit.…”
Section: Introductionmentioning
confidence: 99%